2016
DOI: 10.1515/hepo-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of extracts and their fractions from three Eryngium L. species

Abstract: S u m m a r yIntroduction: Due to increasing resistance against antibiotics and antifungal agents, crude plant extracts, fractions, and isolated pure compounds became a new interest as antimicrobial agents. Objectives: The antimicrobial activity of methanolic extracts and fractions of Eryngium planum L., E. campestre L., and E. maritimum L. was evaluated against selected bacteria, yeast and mould, and compared in tested Eryngium species and in their organs. Methods: The antimicrobial activity was studied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…This observation was in a great agreement with the study of Kholkhal [8], who showed the moderate antibacterial activity of the methanolic extract from the E. maritimum root against S. aureus. The methanolic extract of roots and saponin-phenolic acid fraction of this extract were the most active against C. albicans [37]. The results of Meot-Duros studies on the E. maritimum antimicrobial activity of the leaf hydromethanolic extracts, measured by microdilution method, showed that apolar fractions were more active than polar fractions.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This observation was in a great agreement with the study of Kholkhal [8], who showed the moderate antibacterial activity of the methanolic extract from the E. maritimum root against S. aureus. The methanolic extract of roots and saponin-phenolic acid fraction of this extract were the most active against C. albicans [37]. The results of Meot-Duros studies on the E. maritimum antimicrobial activity of the leaf hydromethanolic extracts, measured by microdilution method, showed that apolar fractions were more active than polar fractions.…”
Section: Resultsmentioning
confidence: 89%
“…The antimicrobial activity of E. maritimum as well as E. planum and E. campestre has been already studied [36,37]. However, it was the extracts and their fractions that were examined, not the essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…This plant belongs to the Apiaceae family. The different components of eryngium include flavonoids, phenolic acids, and coumarins which are key factors of the pharmacological property of this plant [ 106 , 107 , 108 , 109 , 110 ]. Based on the presence of this component, eryngium shows high antimicrobial and antioxidant activity.…”
Section: Antimicrobial Agentmentioning
confidence: 99%
“…The extracts from L. flos-cuculi demonstrated moderate and relatively uniform antifungal activity, with an MIC in range of 1.25–2.5 mg/mL. Similar antifungal activity assays performed on methanolic extracts from leaves and roots of Eryngium planum , Eryngium campestre , and Eryngium maritimum demonstrated less potent antifungal activity against Candida albicans (MIC above 12.5 mg/mL) and Aspergillus niger (MIC above 25 mg/mL) [ 32 ]. Interestingly, aqueous ethanolic extracts from the same material exerted significantly higher activity, with the MIC ranging from 0.04 to 1.9 mg/mL, especially against Trichophyton mentagrophytes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%